ALIRAN LALU LINTAS DAN JARAK GAP OPTIMAL PADA PERSIMPANGAN T - Erwin Kusnandar (Jurnal Jalan-Jembatan, 2005)
Track of traffic flow crossing an uncontrolled T junction creates some conflict points and potentially as traffic accident site. This condition caused the maneuver of vehicles whereas crossing, merging and diverging conflict. Merging vehicle to mainstream vehicle run in a queue need a sufficient distance of gap in order to joint safely. The judgment of accepting or re fusing a distance of gap mostly depend on the decision of the driver which is not according to the priority and by forcing. This situation where as the angle form by the merging vehicle is smaller than 30 degrees will mostly accept by the driver than greater than 30 degrees. This has been proved according the result of empirical research carried out in several road links which type is 4 lanes, 2 direction. Merging with angle smaller than 30 degrees can be accepted if the exit road from the junction has been provided with taper or weaving section.